Năng lực sức khỏe số của học sinh trung học cơ sở tại địa bàn Hà Nội - Ngô Thanh Thủy; Phạm Văn Huệ; Nguyễn Xuân An; Trịnh Vân Hà; Nguyễn Lê Thanh Vân (Tạp chí Giáo dục, 2026)
The rapid proliferation of digital technologies and online platforms has exposed adolescents and secondary school students in particular to an overwhelming volume of health-related information. As a result, eHealth literacy has emerged as a subject of considerable scholarly interest in recent years. Nevertheless, research exploring this competency among secondary school students in Vietnam remains limited in both breadth and depth. This study examines the current state of eHealth literacy among junior high school students in Hanoi and investigates whether significant differences exist across demographic variables and patterns of digital device use. The study employs the Transactional Model of eHealth Literacy instrument developed by Paige et al. (2018), utilising the Vietnamese-adapted version validated for adolescents by Nguyen et al. (2023), which encompasses four constituent competency dimensions. The toolkit was reviewed by Psychologist and School Counselors to ensure the language was appropriate for students. Data were collected 221 valid responses from junior high school students across Hanoi. Drawing on descriptive statistics, independent-samples t-tests, and one-way ANOVA, the findings indicate that the overall eHealth literacy of secondary school students remains moderate. Among the four sub-dimensions, critical literacy recorded the highest mean score, while communicative literacy returned the lowest. Regarding group differences, the analysis revealed that grade level was the only variable to reach statistical significance. In contrast, gender and daily screen time did not produce significant differences in eHealth literacy scores. The findings provide a scientific foundation for secondary schools to design and implement digital health education initiatives integrated into the curriculum, with a strategic priority placed on sixth-grade students. Furthermore, the study contributes to shifting students’ paradigm regarding digital device management, transitioning from traditional screen-time restriction toward the regulation of content exposure and online interaction modalities.